2017
DOI: 10.1038/s41598-017-14229-8
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania infantum lipophosphoglycan induced-Prostaglandin E2 production in association with PPAR-γ expression via activation of Toll like receptors-1 and 2

Abstract: Lipophosphoglycan (LPG) is a key virulence factor expressed on the surfaces of Leishmania promastigotes. Although LPG is known to activate macrophages, the underlying mechanisms resulting in the production of prostaglandin E2 (PGE2) via signaling pathways remain unknown. Here, the inflammatory response arising from stimulation by Leishmania infantum LPG and/or its lipid and glycan motifs was evaluated with regard to PGE2 induction. Intact LPG, but not its glycan and lipid moieties, induced a range of proinflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 67 publications
2
44
0
Order By: Relevance
“…Like other pathogens, some studies reported the participation of TLR in parasite‐induced LDs, as the case of TLR‐2 in the T. cruzi infection, which is amplified by the uptake of apoptotic cells in a mechanism dependent on integrins and TGF‐β synthesis . Moreover, the activation of TLR‐1 and TLR‐2 by Leishmania infantum lipophosphoglycan induced LDs accumulation in association with PPAR‐γ expression . On the other hand, LDs biogenesis was related to dysregulate host metabolism by the subversion of host mTOR and JNK signaling in the T. gondii and N. caninum infection .…”
Section: Lds and Protozoan Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like other pathogens, some studies reported the participation of TLR in parasite‐induced LDs, as the case of TLR‐2 in the T. cruzi infection, which is amplified by the uptake of apoptotic cells in a mechanism dependent on integrins and TGF‐β synthesis . Moreover, the activation of TLR‐1 and TLR‐2 by Leishmania infantum lipophosphoglycan induced LDs accumulation in association with PPAR‐γ expression . On the other hand, LDs biogenesis was related to dysregulate host metabolism by the subversion of host mTOR and JNK signaling in the T. gondii and N. caninum infection .…”
Section: Lds and Protozoan Interactionsmentioning
confidence: 99%
“…47 Moreover, the activation of TLR-1 and TLR-2 by Leishmania infantum lipophosphoglycan induced LDs accumulation in association with PPAR-expression. 188 On the other hand, LDs biogenesis was related to dysregulate host metabolism by the subversion of host mTOR and JNK signaling in the T. gondii and N. caninum infection. 61 Furthermore, T. gondii promotes the expression of some triglyceride synthesis genes and lipid transporters, and inhibits the expression of lipolytic genes, especially ATGL, favoring the LD accumulation in the host cell.…”
Section: Lds and Protozoan Interactionsmentioning
confidence: 99%
“…LPG is one of the major surface glycoconjugates of Leishmania promastigotes and plays a central role in the establishment of infection (17). Importantly, macrophages secrete several immune mediators following exposure to purified LPG (25)(26)(27)(28). Therefore, we hypothesized that this virulence factor could be implicated in the upregulation of CXCL16 in L. donovani-infected macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, LPG prevents phagosome maturation (20), inhibits phagosomal acidification and oxidative burst (21,22), reduces the phagocytic capacity of host macrophages (23), and hampers the lytic action of the complement system (24). In addition to its inhibitory effects, extensive work supports the notion that LPG alters macrophage signaling and contributes to the inflammatory response triggered during Leishmania infection (25)(26)(27)(28)(29). For example, L. mexicana LPG stimulates the synthesis of TNF, interleukin-1␤ (IL-1␤), IL-12, and nitric oxide (NO) through the activation of extracellular signal-regulated kinase 1/2 (ERK1/2) and p38 mitogen-activated protein kinase (MAPK) signaling (28).…”
mentioning
confidence: 97%
See 1 more Smart Citation